(untitled) (Medicine Today, 2017)
The safety and efficacy of oral azithromycin and topical adapalene are well documented. In this study, concomitant use of oral azithromycin pulse therapy and daily topical adapalene in the treatment of acne vulgaris is assessed. A total of 37 patients fulfilled the inclusion criteria were enrolled. Azithromycin, 500 mg orally once daily first 3 days of 10 days’ cycle for 9 cycle & topical Adapalene (0.5%) at night. Patients evaluated at 4 weeks’ interval by using Michaelsson acne severity index. The overall assessment was made by percent reduction of acne lesions and severity score. At the end of 12 weeks’ treatment 99.8% of comedones, 98.7% papular lesion, 94.3% pustular lesion and 88.8% infiltrated lesion were cleared. Only 2.9% cystic lesion responded to the regimens. Percent reduction of Michaelsson acne severity index was 87%, which was statistically highly significant. Overall assessment revealed acne lesion cleared in 22% cases, excellent improvement observed in 65% and 13% showed good response. Adverse effect was minimal. So, azithromycin pulse therapy and topical adapalene is indeed effective and safe in the treatment of acne vulgaris. Medicine Today 2016 Vol.28(2): 52-56